Combination of in silico and molecular techniques for discrimination and virulence characterization of marine Brucella ceti and Brucella pinnipedialis - Girault, Guillaume; Freddi, Luca; Jay, Maryne; Perrot, Ludivine; Dremeau, Alexandre; Drapeau, Antoine; Delannoy, Sabine; Fach, Patrick; Ferreira Vicente, Acacia; Mick, Virginie; Ponsart, Claire; Djokic, Vitomir (Frontiers in Microbiology, 2024)
Mammals are main hosts for Brucella sp., agents of worldwide zoonosis. Marine cetaceans and pinnipeds can be infected by Brucella ceti and B. pinnipedialis, respectively. Besides classical bacteriological typing, molecular approaches such as MLVA, MLSA and Whole Genome sequencing (WGS) can differentiate these species, but are cumbersome to perform. We compared the DNA and genome sequences of 12 strains isolated from nine marine mammals, with highly zoonotic B. melitensis, B. abortus, B. suis and publicly available genomes of B. ceti and B. pinnipedialis. In silico pipelines were used to detect the antimicrobial resistances (AMR), plasmid and virulence genes (VG) by screening six open-source and one home-made libraries. Our results show that easier-to-use HRM-PCR, Bruce-ladder and Suis-ladder, can separate marine Brucella sp. and results are fully concordant with other molecular methods, such as WGS. However, Restriction Fragment Length Polymorphism (RFLP) method cannot discriminate between B. pinnipedialis and B. ceti B1-94 like isolates. MLVA-16 results divided the investigated strains into 3 clades according to their preferred host, which was confirmed in WGS. In silico analysis didn’t find any AMR and plasmid genes, suggesting antimicrobial susceptibility of marine Brucella, while presence of VGs btpA gene was variable dependent of clade. The HRM-PCR and Suis-ladder are quick, easy and cost-effective methods to identify marine Brucella sp. Moreover, in silico genome analyses can give useful insights into the genetic virulence and pathogenicity potential of marine Brucella strains.